1995
DOI: 10.1128/jb.177.14.3998-4008.1995
|View full text |Cite
|
Sign up to set email alerts
|

Virulence factors are released from Pseudomonas aeruginosa in association with membrane vesicles during normal growth and exposure to gentamicin: a novel mechanism of enzyme secretion

Abstract: Pseudomonas aeruginosa blebs-off membrane vesicles (MVs) into culture medium during normal growth. Release of these vesicles increased approximately threefold after exposure of the organism to four times the MIC of gentamicin. Natural and gentamicin-induced membrane vesicles (n-MVs and g-MVs, respectively) were isolated by filtration and differential centrifugation, and several of their biological activities were characterized. Electron microscopy of both n-MVs and g-MVs revealed that they were spherical bilay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
660
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 588 publications
(697 citation statements)
references
References 54 publications
24
660
0
2
Order By: Relevance
“…These environments often have high concentrations of extracellular DNA as a result of cell lysis, although some bacteria actively secrete DNA through type IV secretion systems or membrane vesicles (Hamilton & Dillard, 2006;Kadurugamuwa & Beveridge, 1995). It has been estimated that the lysis of a single cell can increase local DNA concentrations to above 100 mg ml 21 (Baur et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…These environments often have high concentrations of extracellular DNA as a result of cell lysis, although some bacteria actively secrete DNA through type IV secretion systems or membrane vesicles (Hamilton & Dillard, 2006;Kadurugamuwa & Beveridge, 1995). It has been estimated that the lysis of a single cell can increase local DNA concentrations to above 100 mg ml 21 (Baur et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, under normal cellular growth conditions, the accumulation of OMPs should not be a serious problem in a bacterial cell, because they are diluted upon bacterial growth and division as new OMPs are biosynthesized [18]. In addition, Escherichia coli and other Gram-negative bacteria dispose of their outer membranes by blebbing off outer membrane vesicles whose composition includes outer membranes, outer membrane proteins and periplasmic components [19][20][21].…”
Section: Introduction: the Challenges Of Unfolded Outer Membrane Protmentioning
confidence: 99%
“…It has been suggested that anionic repulsion between neighboring LPS molecules induces MV production in Gram-negative bacteria (12). Because PQS strongly interacts with LPS (26), the anionic repulsion is considered to be enhanced by the addition of PQS, resulting in increased MV production.…”
Section: Effects Of Magnesium On MV Productionmentioning
confidence: 99%